MAKNA GERAK KONTEKSTUAL TARI KAIN DI PAUH LIMO KECAMATAN PAUH KOTA PADANG - Rahmadani, Azura; Susmiarti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the contextual meanings of movements in the Kain Dance of Pauh Limo, Pauh District, Padang City, using a qualitative descriptive approach. Data were collected through literature review, observation, interviews, and documentation, utilizing both primary and secondary data. The results show that each movement in the Kain Dance contains meanings closely related to the Minangkabau worldview. The Opening Sambah movement symbolizes surrender to God and respect for nature and fellow human beings, while the worship toward the four directions reflects balance within social space. The Sambah movement signifies beginning an action in an orderly and conscious manner; Gantuang Sabalah represents caution; Rantak Tigo symbolizes the human life cycle; Malapia reflects courage to act; Mailak illustrates intelligence in avoiding danger; Kalatiak denotes wise resistance to pressure; and Mangepo represents firm self-defense. Overall, the Kain Dance functions not only as a traditional dance but also as a medium for conveying life values within Minangkabau customary culture.